2015
DOI: 10.1002/cyto.a.22652
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying autophagosomes and autolysosomes in cells using imaging flow cytometry

Abstract: Autophagy dysregulation has been implicated in numerous diseases and many therapeutic agents are known to modulate this pathway. Therefore, the ability to accurately monitor autophagy is critical to understanding its role in the pathogenesis and treatment of many diseases. Recently an imaging flow cytometry method measuring colocalization of microtubule associated protein 1B light chain 3 (LC3) and lysosomal signals via Bright Detail Similarity (BDS) was proposed which enabled evaluation of autophagic processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Recent publications have emphasized the need to examine the concurrent formation of the autolysosome 2 17 20 21 . MIFC is uniquely able to measure the formation of the autolysosome by imaging the co-localization of the autophagosome to the lysosome 15 - 17 20 21 22 23 24 25 26 . In addition, the co-localization of p62 and LC3 using MIFC has also been explored to measure autophagic flux 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent publications have emphasized the need to examine the concurrent formation of the autolysosome 2 17 20 21 . MIFC is uniquely able to measure the formation of the autolysosome by imaging the co-localization of the autophagosome to the lysosome 15 - 17 20 21 22 23 24 25 26 . In addition, the co-localization of p62 and LC3 using MIFC has also been explored to measure autophagic flux 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient is log-transformed to increase the range to between zero and infinity 26 27 . BDS alone may not be sufficient; Rajan et al found that using only BDS could lead to false-positive or false-negative results 21 . BDS evaluates the co-localization of two markers of autophagy but does not consider the number of autophagosomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He received this highest honor for his discoveries of mechanisms for autophagy (nobelprize.org; ). This is a good sign for Cytometry that did play a relevant role in his discoveries .…”
mentioning
confidence: 76%
“…These regulatory processes are often studied in cancer cells because they require staged intracellular mechanisms, which if fully understood can be exploited as therapeutic targets. Cytometry as a multiparametric tool has been employed for decades to study these mechanisms (see a few recent publications on these subjects in References ), and the publications we highlight herein exemplify modern approaches toward that end.…”
mentioning
confidence: 99%